Pengaruh Program Keluarga Harapan terhadap Kesejahteraan Masyarakat di Kecamatan Kubung Kabupaten Solok - Mardaus Mardaus (Journal of Education on Social Science (JESS), 2023)
Poverty and the level of social welfare are often problems that are often faced by every country. Various efforts, both in the form of programs and policies, have been made by the government to overcome this problem. In Indonesia, one of the efforts to overcome this problem is to issue a Family of Hope (PKH) policy and program. So the purpose of this article is to discuss the effect of the family hope program on people's welfare. This research uses quantitative methods with associative quantitative types. Data collection was carried out using a Likert scale questionnaire supported by a documentation study. Using the Simple Random Sampling technique and the Yamane formula, a sample of 61 respondents was determined. Regression analysis is used to analyze field data that has previously been tested with classical assumptions. The results showed that the Family Hope Program (PKH) positively and significantly affects the welfare of the people in Kubung District, Solok Regency, with an influence contribution of 0.315 or 31.5%.